2018
DOI: 10.4149/neo_2018_180122n48
|View full text |Cite
|
Sign up to set email alerts
|

SLC27A2 regulates miR-411 to affect chemo-resistance in ovarian cancer

Abstract: Although platinum-based chemotherapies have long been used as standard treatment in ovarian cancer, cisplatin resistance is a major problem that restricts its use. Herein, we investigate the biological function of SLC27A2 and its underlying mechanisms in regulating chemo-resistance in ovarian cancer. The findings show that SLC27A2 down-regulation in primary ovarian cancer tissues correlates with chemo-resistance and poor patient survival in our patient cohort. Significantly, we demonstrate that up-regulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…4d), resembling a pattern of loss-of-function mutations, usually characteristic of tumor suppressor genes. This finding may be consistent with a predominantly tumor suppressor role and downregulation of miR-411-5p and miR-411-3p in different cancers, including glioblastoma, breast cancer, ovarian cancer, lung adenocarcinoma, bladder cancer and renal cell carcinoma [83][84][85][86][87] . For example, miR-411-5p suppresses cell growth, migration, and invasion, and its downregulation correlates with lymph node metastasis in breast cancer 84 and contributes to chemoresistance in ovarian cancer 88 .…”
Section: Hsa-mir-411supporting
confidence: 74%
“…4d), resembling a pattern of loss-of-function mutations, usually characteristic of tumor suppressor genes. This finding may be consistent with a predominantly tumor suppressor role and downregulation of miR-411-5p and miR-411-3p in different cancers, including glioblastoma, breast cancer, ovarian cancer, lung adenocarcinoma, bladder cancer and renal cell carcinoma [83][84][85][86][87] . For example, miR-411-5p suppresses cell growth, migration, and invasion, and its downregulation correlates with lymph node metastasis in breast cancer 84 and contributes to chemoresistance in ovarian cancer 88 .…”
Section: Hsa-mir-411supporting
confidence: 74%
“…For example, lncRNA MALAT1 was highly expressed in OV cells and accelerated the invasion and proliferation in OV 8 . LncRNA SLC27A2 affected chemoresistance of OV to cisplatin via modulating miR‐411 9 . LINC00319 boosted OV development via targeting miR‐423‐5p/NACC1 axis 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The downregulation of PML is related to the occurrence and development of high-grade tumors [ 51 ]. In endometrial and ovarian cancer, researchers found that SLC27A2 can play a biological role in regulating chemical resistance [ 52 , 53 ]. EHHADH can encode a bifunctional enzyme and is one of the four enzymes for peroxisomal β -oxidation [ 54 ].…”
Section: Discussionmentioning
confidence: 99%